PERFORMANCE ANALYSIS OF COMPANY SHARES AFTER CONDUCTING INITIAL PUBLIC OFFERING ON THE JAKARTA STOCK EXCHANGE - Lastari, Siwi (Accounting, 2010)
This was an event study on the performance of stocks after the company conducted an IPO on the JSE. The goal is to find out what happened phenomenon outperformed short-term stock performance to what happened three months and underperformed the phenomenon of long-term stock performance for two years. Performance is measured by stock returns in the development of this research using the abnormal return. The samples were manufacturing companies in initial public offering period 1997-2001 a total of 27 companies. This method study using secondary data through the methods of documentation and literature. Data needed taken through the Indonesian Capital Market Directory (ICMD), JSX Statistics, http://www.finance.com, http://www.bkpm.go.id.. As for the long-term phenomenon occurred two years also outperformed the stock performance, indicated by a positive abnormal return of 1.42% but the performance increase was not significant, so the results of both studies do not support previous research that shows the long-term phenomenon underperformed (decrease in performance with with a negative abnormal return). Keyword : Stock Exchange, ICMD, JSX